In‐depth adaptation of winter wheat cultivation technology in the Central Chernozem region - I. I. Gureev; L. B. Nitchenko; I. A. Prushcik (Юг России: экология, развитие)
Aim. The purpose of the research is to determine the method of soil cultivation and the dose of NPK, based on in‐depth adaptation of winter wheat cultivation technology, ensuring the minimum cost of producing grain of the crop of the required quality in the Central Black Earth Region (CBER).Materials and Methods. The efficiency of winter wheat production largely depends on the adaptation of the technology of its cultivation to soil and climatic conditions, which are identified at the level of the agroecological province. But the main object of farming systems ‐ the soil cover within the agroecological province is distinguished by a high territorial diversity in fertility, which is not taken into account when developing agricultural technologies and thus lowers the level of their adaptability. Therefore, it is proposed to minimize the use of resources in intensive technologies due to in‐depth adaptation of tillage and fertilization in accordance with the initial state of the soil of a particular field.Results. It was found that for the conditions of the CBER, the optimal values of the factors are the dose N19P39K39 and the combined method of tillage for winter wheat, which correspond to the minimum cost of grain of 5.38 thousand roubles/t with a yield of 3.38 t/ha and a 12% protein content in grain of 3rd class.Conclusion. In addressing agricultural problems when there is an interaction between the factors, the effectiveness of in‐depth adaptation increases with the complex optimisation of factors according to innovative methodology using the mathematical method of indefinite Lagrange multipliers. Comprehensive optimisation of the factors made it possible to determine the method of tillage and the dose of fertiliser that would ensure the minimum cost of producing grain of a given quality under the conditions of the CBER.